Nondysraphic Intramedullary Cervical Cord Lipoma with Exophytic Component: Case Report - Ahmed, Osama; Zhang, Shihao; Thakur, Jai Deep; Nanda, Anil (Journal of Neurological Surgery Reports, 2015)
Introduction Spinal intradural lipoma is a rare condition, accounting for < 1% of all spinal cord tumors. Spinal cord lipomas are frequently associated with dysraphism and occur in the thoracic spine. Another common finding is that spinal cord lipomas tend to present in the pediatric population. Isolated nondysraphic cervical lipomas are a rare entity. We discuss a case of nondysraphic cervical lipoma with an exophytic component.Case A 31 year-old woman presented with bilateral numbness in her hands and a burning and aching sensation in her arms for ∼ 6 months. The patient did not have any weakness or myelopathic signs. Magnetic resonance imaging T1 showed a T1 hyperintense, T2 hypointense, non–contrast-enhancing mass on the dorsal aspect of the spinal cord with significant compression. The patient underwent a dorsal cervical laminectomy with subtotal resection of an isolated cervical lipoma with an exophytic component. The pathology confirmed the diagnosis of a lipoma.Conclusions Surgical management of this rare pathology has a wide variety of options. Depending on the neurologic deficits, observation to gross total resection may be reasonable options. In our case, a subtotal resection was achieved with no further worsening of neurologic symptoms.
Keywords: intramedullary spinal cord neoplasm; lipoma; cervical cord neoplasm